Inaugural Editorial - John O'Neill; Paul Adams (New Zealand Journal of Teachers' Work)
Our intention in launching this journal is to provide a virtual collegial forum in which teachers, researchers, policymakers and others with an interest in teaching can safely document and explore the complexity of teachers